(untitled) (Nigerian Journal of Technology, 2023)
Reactive Powder Concrete (RPC) is one of the latest developments in the field of concrete technology and contains about 20% to 25% silica fume and fibre which are not readily available in Nigeria. The research aims at evaluating the effect of incorporating unrefined metakaolin (MK) as substitute of silica fume and gear inner wire (GIW) as fibre on the properties of the RPC using Analysis of Variance (ANOVA). The quantity of the GIW was fixed at 0.25% (by weight of concrete) while that of MK was 10%, 20% and 30% of the cementitious materials. The study considered GIW and MK as factors while compressive, tensile and flexural strengths as responses. The ANOVA of test results depicted that the two factors (unrefined MK & GIW) have significant effect on compressive strength, tensile strength and flexural strengths of the RPC. Moreover, there are substantial influences of interaction of two factors on the selected properties of the RPC. Therefore, unrefined MK and GIW are suitable in the production of RPC.